ASSESSMENT OF DEPRESSION SEVERITY AND QUALITY OF LIFE AMONG OUTPATIENTS WITH DIABETES MELLITUS AT A GENERAL HOSPITAL IN HANOI: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the level of depression and quality of life among outpatients with diabetes mellitus at MEDLATEC General Hospital, Hanoi.Subjects and methods: A cross-sectional descriptive study with analytical components was conducted on 252 outpatients aged ≥ 18 years with diabetes mellitus from April to May 2025. Depression was assessed using the PHQ-9 scale, and quality of life was evaluated using the AsianDQOL instrument. Data were analyzed using SPSS version 22.0 software. Results: The study revealed that the prevalence of depression among outpatients with diabetes mellitus was 15.5%, with prominent symptoms including fatigue, sleep disturbances, and impaired concentration. Additionally, the majority of patients (88.9%) had suboptimal quality of life, with the domain of personal relationships being the most adversely affected. Conclusion: The findings highlight the need for early detection of depression and targeted interventions to improve factors associated with quality of life, particularly aspects related to patients’ personal relationships.
Keywords: Diabetes mellitus, depression, quality of life, PHQ-9, AsianDQOL.